THEME: REAL-WORLD PRACTICE AND EXPERIENTIAL LEARNING: BRIDGING THEORY AND APPLICATION - Safarova Dildora,; Xaidboyeva Durdona, (Ustozlar uchun, 2025)
This article explores the significance of real-world practice and experiential learning in modern education. It emphasizes the need to move beyond traditional theoretical instruction by engaging learners in hands-on, practical experiences that mirror real-life challenges. The article discusses the benefits of experiential learning, such as deeper understanding, skill development, increased student motivation, and better career preparation. It also highlights how experiential learning fosters critical thinking, collaboration, and adaptability. By reflecting on these experiences, students gain insights that reinforce their academic knowledge and enhance their ability to apply it in various contexts. The article concludes that experiential learning is essential for preparing students to meet the demands of the 21st-century workforce and society.